Trends of carbon dioxide (CO2) emissions from fossil fuels combustion (coal, gas and oil) in the EU member states from 1960 to 2018. (December 2020) - Paraschiv, Spiru; Paraschiv, Lizica Simona
Abstract: The paper analyzes the variation of carbon dioxide emissions produced by burning fossil fuels for energy production in the European Union member states between 1960 and 2018. It was analyzed the evolution of CO2 emissions produced by the combustion of coal, gas, and oil in 28 member states. The analysis showed that Cyprus, Portugal, Greece, and Spain recorded the highest increases in CO2 emissions in 2018 compared to 1960, while the Czech Republic and Latvia recorded the lowest increase in CO2 emissions by only 7% compared to 1960. Only four countries (Germany, Luxembourg, Sweden, and the United Kingdom), out of the 28 countries analyzed, had in 2018, CO2 emissions lower than or equal to those of 1960. In 2018, CO2 emissions generated by burning coal increased in eleven countries and decreased in the other seventeen countries, compared to 1960 emissions. CO2 emissions from gas combustion increased in all 28 countries analyzed, with the mention that in 1960, eleven countries had no gas consumption. Regarding the CO2 emissions generated by oil burning, they have increased in 26 countries and only two countries have registered emissions reduction below the value of 1960. EU's energy intensity (ratio of gross energy consumption to gross domestic product) decreased by 37% between 1990 and 2017. Graphical abstract: